2016
DOI: 10.1038/nature17041
|View full text |Cite
|
Sign up to set email alerts
|

Protein misfolding in the endoplasmic reticulum as a conduit to human disease

Abstract: In eukaryotic cells, the endoplasmic reticulum is essential for the folding and trafficking of proteins that enter the secretory pathway. Environmental insults or increased protein synthesis often lead to protein misfolding in the organelle, the accumulation of misfolded or unfolded proteins - known as endoplasmic reticulum stress - and the activation of the adaptive unfolded protein response to restore homeostasis. If protein misfolding is not resolved, cells die. Endoplasmic reticulum stress and activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
1,048
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 1,287 publications
(1,065 citation statements)
references
References 126 publications
10
1,048
0
7
Order By: Relevance
“…Thus, based on the composition of constituent genes, module responses were consistent with ER stress and then overload leading the cell death. 33,34 Module changes in rat hepatocyte treated with tunicamycin and ethionamide were similar including the four ER stress modules in C.I.b (Supplementary Figure S3). Treating rat primary hepatocytes with ethionamide increased Atf4, Hspa5 and Hsp90b1 protein and processing of Atf6 to the transcriptionally active form, evidence of ER stress (Figure 3d).…”
Section: Resultsmentioning
confidence: 81%
“…Thus, based on the composition of constituent genes, module responses were consistent with ER stress and then overload leading the cell death. 33,34 Module changes in rat hepatocyte treated with tunicamycin and ethionamide were similar including the four ER stress modules in C.I.b (Supplementary Figure S3). Treating rat primary hepatocytes with ethionamide increased Atf4, Hspa5 and Hsp90b1 protein and processing of Atf6 to the transcriptionally active form, evidence of ER stress (Figure 3d).…”
Section: Resultsmentioning
confidence: 81%
“…These findings revealed that the luminal ATF6 [Y567N] mutation resulted in the impairment of ATF6 signaling in ATF6 Y567N/Y567N fibroblasts during ER stress. ATF6 signaling is a key component of the unfolded protein response (UPR) and operates in parallel with UPR signal transduction pathways controlled by the inositol-requiring enzyme 1 (IRE1) and PKR-like endoplasmic reticulum kinase (PERK) proteins to ensure normal ER function in mammalian cells (11,12). We next examined whether the other branches of the UPR were also dysregulated in ATF6 Y567N/Y567N fibroblasts.…”
Section: Y567n/y567nmentioning
confidence: 99%
“…Folding‐deficient proteins are labeled with specific mannose residues for ERAD degradation. Increased ER stress causes many human diseases,10 including cancers 11. Recent studies have demonstrated that the overexpression of α‐1,2‐mannosidase accelerates ERAD 12, 13…”
Section: Introductionmentioning
confidence: 99%